The law and politics of international regime conflict - Pulkowski, Dirk (Oxford : Oxford University Press, 2014)
Conflict can occur when a body of law regulating one aspect of international activity does not correspond with the rules of another. This book uses trade in cultural products to illustrate that, rather than being a question of accidental overlap, such conflicts stem from different regimes having fundamentally different goals.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on March 14, 2014).
Keywords: International regimes; International regimes -- Political aspects